Experimental study of gas-brine capillarity measurement at high temperature and pressure - Sidiq, Hiwa (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Understanding capillary pressure profiles during gas-brine coreflooding is essential for analyzing fluid behavior in porous media, particularly in gas reservoirs. Direct measurement of capillary pressure in dynamic displacement experiments relies on evaluating the balance between capillary forces and pressure gradients within the porous structure. In this experimental study three rock samples were taken from a natural gas reservoir located on Australia's Northwest Shelf. Experiments were conducted under simulated reservoir conditions (~ 41.37 MPa and 368.15 K) to investigate the effects of pore size, porosity, and water saturation on the capillary pressure profile. The capillary pressure curves (Samples C1–C3) reveal distinct dynamic behaviors. Samples C1 and C2, which have higher permeability and porosity, exhibit an initial decrease followed by a monotonic rise in capillary pressure until breakthrough. In contrast, Sample C3, characterized by lower permeability and porosity, shows lower brine saturation. However, higher brine saturation would typically be expected in low-porosity samples due to increased grain surface area and smaller pore throats that trap the wetting phase. This unexpected result is attributed to the experiments being conducted under high-pressure and high-temperature conditions. These findings underscore the critical role of pore geometry in governing displacement efficiency and capillary trapping. They also provide valuable quantitative insights for reservoir modeling, particularly in predicting gas recovery under HPHT conditions where capillary forces are significant.